Improvement of Knowledge and Understanding of Green Leadership for Employees of BPR Restu Artha Makmur - Dian Wishnu Brata; Lisa Ardaniyati; Contantinus Contantinus; Hermiana Vereswati (Institut Teknologi dan Bisnis Asia Malang, 2023)
Purpose: This research paper explores the success of PT BPR Restu Artha Makmur, a rural bank founded in Semarang City in September 2003. It focuses on the bank's recognition as the Best Rural Bank in Indonesia for assets ranging from Rp 100 billion to Rp 500 billion by Infobank magazine in March 2013 and its Sixth Best Rural Bank ranking in the same category in June 2014. The study highlights the role of leadership in transforming the bank from a profit-centric institution to one emphasizing financial sustainability, social responsibility, and environmental consciousness. Method: This descriptive case study uses publicly available data, avoiding analytical techniques. Practical Applications: PT BPR Restu Artha Makmur's success story serves as a model for financial institutions aiming to adopt sustainable finance, social responsibility, and environmental awareness. It demonstrates the benefits of such a transformation, offering inspiration for banks looking to integrate green practices and leadership into their operations. Conclusion: PT BPR Restu Artha Makmur's journey underscores the rewards of green leadership and sustainable finance, showcasing the potential for positive impact and financial sustainability. It serves as a beacon for financial institutions seeking to embrace sustainability and responsible practices.